2004
DOI: 10.1097/00001199-200411000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Explanatory Model of Social Participation for Adults With Traumatic Brain Injury

Abstract: Resiliency factors constitute a target for research and intervention for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 56 publications
0
31
0
4
Order By: Relevance
“…In the chronic stage after brain injury, this positive association was already known. 6,7,9 Furthermore, increasing self-efficacy seemed to mitigate the negative influence of emotion-oriented coping on health-related QOL, suggesting that high self-efficacy has a protective effect. This stress-buffering effect of high self-efficacy is well documented in healthy people 33 and patients with cancer.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the chronic stage after brain injury, this positive association was already known. 6,7,9 Furthermore, increasing self-efficacy seemed to mitigate the negative influence of emotion-oriented coping on health-related QOL, suggesting that high self-efficacy has a protective effect. This stress-buffering effect of high self-efficacy is well documented in healthy people 33 and patients with cancer.…”
Section: Discussionmentioning
confidence: 96%
“…6 As a general concept, higher general self-efficacy has been related to better QOL and social participation in TBI. [7][8][9] However, because all studies were conducted cross-sectionally in the chronic stage after TBI, one cannot determine whether self-efficacy in the early stage after brain injury is predictive for better long-term QOL and social participation.…”
mentioning
confidence: 99%
“…Previous studies have shown that personal factors such as perceived self-efficacy, determination, will, motivation and 'dynamism' are related to positive outcomes following TBI [38,39]. These factors are specifically related to increased social participation (including recreation, inter-personal involvement and community engagement) [38] and higher employment rates [39]. The results of the current study were consistent with previous findings, in that men who conformed to the masculine role of winning and pursuit of status also demonstrated better functional outcomes, as measured by the FIM.…”
Section: Discussionmentioning
confidence: 99%
“…Salutogenesis calls also for a focus on resources, skills, capabilities, strengths, and assets at different levels (e.g., people, community, and society; Dumont, Gervais, Fougeyrollas, & Bertrand, 2004;Roy & O'Neill, 2012). Following this thought, Lindström and Eriksson (2008) introduced a salutogenic perspective under a salutogenic umbrella where all theories and/or concepts in relation with positive health were gathered.…”
Section: The Evolution Of Salutogenesismentioning
confidence: 99%